Frequency Discrimination Method Using Asymmetric Transmission Time in FSK Radar - Jae Young Sim; Jong-Ryul Yang (Journal of Electromagnetic Engineering and Science, 2022)
A frequency discrimination method based on transmission time control is proposed for effective absolute distance measurement using frequency-shift keying (FSK) radar. In FSK radar, each frequency is transmitted for different durations using an asymmetric control signal. The phase difference at each frequency is effectively obtained by counting the different numbers of samples obtained after envelope detection in the baseband signal. The proposed method can easily and rapidly distinguish the phase difference for each frequency. This makes it simple to measure the absolute distance up to the maximum unambiguous range. The absolute distance measured using FSK radar with a frequency spacing of 150 MHz showed an accuracy of 97.08% in the full unambiguous range. The distance measurement results prove that the proposed method using FSK radar is useful for presenting the maximum unambiguous range.